The effects of luck perception on consumer variety-seeking - Jianbin Zhao; Zheng Li (PLoS ONE, 2025)
Companies often use luck, which is thought to be a psychological force, as a marketing tool to perform marketing activities. This paper designed three experiments to verify the effects of luck perception on variety-seeking. Experiment 1 found that luck perception allows consumers to have more variety-seeking. Experiment 2 examined the mediating role of novelty-seeking motivation and found that luck perception improves the novelty-seeking motivation and makes consumers prefer variety-seeking. Experiment 3 examined the moderating role of need for cognitive closure. For consumers who have low need for cognitive closure, whether prime luck perception or not, their variety-seeking are not significantly different, while for consumers with high need for cognitive closure who are after luck perception primed, they have more variety-seeking. This study provides theoretical support for understanding luck scientifically and enlightens and guides companies to expand product lines, present new brands, and implement precision marketing.